Pre-hospital care in Ilorin: a call for action. (7th October 2012) - Ofoegbu, C; Nasir, A; Lawal, I; Abubakar, S; Babalola, O; Solagberu, B
Abstract : Background: Many fatal injuries may be prevented or their severity reduced by adequate prehospital trauma care. Lack of emergency medical services in Nigeria accounted for significant mortality and morbidity. Aims/Objectives/Purpose: To evaluate quality and availability of pre-hospital trauma care in Ilorin, Nigeria. Methods: A prospective study was undertaken at the emergency room (ER) over 4 months period. Intervention at site of injury, mode of transportation, intervention during transportation, person who brought patient to the hospital and injury arrival time was recorded. Data was analysed with SPSS 15.0 Results: A total of 151 patients were included, of which 126 (83.4%) were male. Most injuries 84.8% (n=128) occurred on highway/street. Traffic crashes accounted for 72.2% (109). Only six (4.5%) patients had intervention at the site of injury (four had splinting and two cleansing of external wounds). Only two (1.5%) patients had fracture splinting provided during transport. Patients were brought to hospital by relatives (81, 53.6%), Police/Federal road safety corps (33, 21.8%) and bystanders (24, 15.9%). Only 75 patients had documentation of mode of transport: public vehicles (41, 54.7%), private cars (23, 30.7%), police/Federal Road Safety Corps patron van (6, 8%). only two (2.7%) patients were transported with ambulances. Sixty-six percent of patients arrived in hospital within 1hrs (70% brought by relatives/bystanders, p=0.0001). Significance/Contribution to Field: This study shows that most injured persons were still first seen and transported by untrained relatives, bystanders or police officers. Training of community members in first respondent care may benefit large numbers of victims of serious and life-threatening injury.